Arsenic contamination of groundwater and its effects on drinking water, irrigation and public health in Bangladesh (Journal of Bangladesh Academy of Sciences, 2025)
Bangladesh is the worst affected country in the world by arsenic contamination of groundwater. The widespread installation of low-cost shallow tubewells, initially intended to control waterborne diseases, has exposed millions to high arsenic concentrations through drinking water. Arsenic (As) in groundwater in the absence of dissolved oxygen is predominantly present as As(III) which is more toxic than As(V). Food, particularly rice, represents another significant pathway of arsenic exposure. Approximately75% of dry-season irrigation relies on groundwater, arsenic accumulation in cropsespecially ricemay substantially contribute to the total body burden in affected areas. The cause, magnitude, and health impacts of arsenic contamination of groundwater have been investigated in many studies. This paper provides an updated synthesis based on available research. The paper also presents a comprehensive analysis of the cause and extent of contamination, andits impacts on drinking water, agro-environment and prevalence of arsenic-related diseases. Arsenic risk management measures implemented in Bangladesh are discussed. The analysis includes estimates of population exposed to varying arsenic concentrations, an assessment of the effects of contaminated irrigation water on soil, paddy plants, and rice grains, and an exploration of the correlation between average drinking water arsenic contents at the Upazila (sub-district) level and the prevalence of arsenicinduced skin lesions in that Upazila.J. Bangladesh Acad. Sci. 49(2); 157-177: December 2025